Eksistensi UMKM dalam Aspek Jaminan/Agunan Kredit serta Perlindungan Hukumnya dan Kebijakan Pemerintah Dalam Rangka Melaksanakan Pembagunan Ekonomi Nasional - Pradinata, Muhammad Justian (Mahesa Research Center, 2023)
This article aims to find solutions for banking services in providing credit to Micro, Small and Medium Enterprises (MSMEs) in Indonesia which are focused on guarantees. The research method used is mixed methods or a combined method of quantitative and qualitative approaches, where both complement each other so that accurate data can be obtained. This article concludes that there are several internal policies from banks in providing credit either guaranteed or unsecured. The government and business actors are trying and jointly looking for a way out so that the country's economic condition remains stable. In the process, it was unexpected that the MSME sector was the only one that could survive even in a state of economic crisis. MSMEs are proven to make a positive contribution to the formation of the Gross Domestic Product (GDP) and also employment. With these facts, the Government through Financial Institutions such as Banking, cooperates in obtaining capital for MSME actors to develop their businesses through credit loans. The solution obtained for MSME actors is that banking institutions will provide credit loans with and or without collateral. For the security aspect for capital lending institutions in terms of unsecured loans, banking institutions will implement an insurance system that works with third parties, where there will be a premium at each stage of payment.